158k views
5 votes
Which function is the inverse of

Which function is the inverse of-example-1

1 Answer

2 votes

Answer:

The answer to your question is f⁻¹(x) =
(1)/(2) x - (3)/(2)

Explanation:

Function

f(x) = 2x + 3

Process

1.- Instead of f(x) write y

y = 2x + 3

2.- Interchange the variables

x = 2y + 3

3.- Solve for y

- Subtract 3 in both sides

x - 3 = 2y + 3 - 3

x - 3 = 2y

- Divide by 2


(1)/(2) x - (3)/(2) = y

4.- Write f⁻¹(x) instead of y

f⁻¹(x) =
(1)/(2) x - (3)/(2)

User Ryskajakub
by
5.1k points